Framtidens kvinna. Framställningen av kvinnlig rösträtt i två svenska flickböcker. (1st January 2017) - Andersson, Maria
ABSTRACT: This article explores depictions of female suffrage and the women's movement in two stories published for girls: Cecilia Milow's "Han eller hon?" (1892, Him or Her?) and Hedvig Svedenborg's Hannas dagbok (1921, Hanna's Diary). My aim is to analyze how representatives of the women's movement are portrayed in the texts and how meeting these women affects the character development of the protagonist. The article shows that both narratives associate the women's movement with modernity. In Milow's text, the main character has to find a balance between a modern, exaggerated version of female liberation and misogynist views of women's subordination. Svedenborg's novel, on the other hand, contrasts different types of female modernity and emancipation, giving priority to women who combine traditionally feminine values with political work as "mothers of society". Despite their ideological differences, both texts address the girl reader as a future political subject by incorporating explicit discussions of women's rights in books for girls.